The Development of an Internal Supervision Model by applying the Professional Learning Community in Bankonadee school. The Primary Educational Service Area Office Amnatcharoen Office of the Basic Education Commission (OBEC) - Puttharagsa, Srisuda (RATANABUTH JOURNAL, 2022)
The objectives of this research were 1) to study the components and indicators of an Internal supervision by applying professional learning community at Bankornadee school. 2) to study the current and desirable condition of an Internal supervision by applying professional learning community at Bankornadee school Overall, the current condition is at a high level and 3) to develop a model and prepare a manual for using the internal supervision model by applying professional learning community at Bankornadee school. 4) to study of the results of using the internal supervision model by applying professional learning community at Bankornadee school. using research methodologies for research and development. The research results found that 1) the results of the study the components and indicators of the internal supervision style by applying professional learning community at Bankornadee school. Overall, suitability was at the highest level. 2) the results of the study of the present and desirable conditions, the internal supervision model by applying professional learning community at Bankornadee school. Found: Overall, the current condition is at a high level and the desirable condition was at the highest level. 3) the results of developing an internal supervision model by applying professional learning community at Bankornadee school by analyzing the needs. In descending order, they are: 1) The study of current conditions, problems and needs. 1) Supervision evaluation. and 3) Supervision operations. 4) The results of using the internal supervision model by applying professional learning community at Bankornadee school. Found: Before the development, the overall practice was at a high level. and after the development, it was found that the overall practice was at the highest level.